Moderasi Manajemen Laba Pada Pengaruh Good Corporate Governance Dan Corporate Social Responsibility Terhadap Kinerja Keuangan - Ireva Suryananingtyas; Rida Perwita Sari; Acynthia Ayu Wilasittha (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The aim of this study was to ascertain the relationship between Good Corporate Governance and Corporate Social Responsibility and financial performance when earnings management was employed as a moderator. A quantitative methodology is used to conduct the research. Listed on the IDX during the period 2020-2022, consumer non-cyclicals companies comprised the research samples. This inquiry has made use of secondary data. The sample technique employed in this experiment was purposeful sampling. Data analysis for this study was done using PLS-SEM, which was assessed using WarpPLS 7.0. The outcomes of the study indicate that neither CSR nor GCG can influence financial performance, nor can earnings management act as a moderate between GCG and financial success. However, the influence of GCG on financial performance can be moderated by earnings management.